Practical Decorative Art Of Surkhan Oasis Residents (Eurasian Journal of History, Geography and Economics, 2024)
The inhabitants of the oasis have always paid great attention to practical decorative arts. Zaroutsoi rock paintings and their diversity continue to amaze people. Art examples embodying the direct connection between material and spiritual culture, artistic monuments created from ancient times to the present are considered the product of the creative outlook of the people who lived in the oasis.